as - Mei Lie; Pujiarti (LPPM UBD, 2024)
The objective of the study was to examine the influence of Coworkers, Work Conflicts, and the Work Environment on Employee Performance at PT Petindo Era Tangguh. The researcher utilized a quantitative descriptive approach, gathering survey data from PT Petindo Era Tangguh employees. The data analysis encompassed assessments of validity, reliability, classical assumptions, statistical models, t-tests, and F-tests. The research results revealed that Coworkers, Work Conflicts, and the Work Environment collectively affect Employee Performance by 48.4% as indicated by the adjusted R Square (R2), while the remaining 51.6% is influenced by other factors. In the t-test results, the Coworker variable (X1) had a value of 5.833, surpassing 2.037, with a significant value of 0.000 (< 0.05), leading to the rejection of Ho and acceptance of Ha. Conversely, the Workplace Conflict variable (X2) showed a value of 0.353, less than 2.037, with a significant value of 0.726 (> 0.05), resulting in the acceptance of Ho and rejection of Ha. Moreover, the Working Environment variable (X3) exhibited a value of 3.313, exceeding 2.037, with a significant value of 0.002 (< 0.05), leading to the rejection of Ho and acceptance of Ha. Additionally, according to the F-test, the Coworker (X1), Workplace Conflict (X2), and Working Environment (X3) variables in relation to Employee Performance (Y) produced a value of 11.642, surpassing 2.679, with a significant value of 0.000 (< 0.05). Thus, Ho was rejected, and Ha was accepted, indicating that the dependent variable simultaneously influences the independent variables.